GHRELIN GENE POLYMORPHISMS AND EXPRESSION BOND WITH SOME GROWTH AND CARCASS TRAITS OF ROSS 308 BROILER CHICKENS - & et al., Joody (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This experiment was conducted to study the association of Ghrelin gene polymorphisms and expression levels with some productive and carcass traits of broiler chickens. Two hundred broiler chicks, one day old Ross308, were wing-tagged and reared under conventional conditions. Blood samples were collected individually of all birds to study of ghrelin gene polymorphisms by PCR-RFLP technique. Proventriculus was collected at 35 days of age from thirty birds of each groups sorted according to high, moderate and low growth rate to measure ghrelin gene expression by real-time RT-PCR. Result revealed that final body weight and weight gain were not significantly influenced by ghrelin gene , whereas body weight and weight gain of males and females with high ghrelin gene expression were significantly (p0.05) influence on carcass traits and edible organ weights, while significant (P < 0.01) differences were existed among high, moderate and low ghrelin gene expression groups  in carcass weight, breast, wing, neck and back relative weights. It is concluded that PCR- RFLP technique revealed no  significant effect for ghrelin gene polymorphisms on productive and carcass traits, whereas ghrelin gene expression had significant effect on productive traits.